Development of a Time-Duration Measure of Continuity of Primary Care: An Application of Econometric Approaches among People with Diabetes - Ha, Thi Ninh (Curtin University, 2019)
This thesis develops a new continuity of care measure, the Cover Index, to better capture the management aspect of continuity of care among people with diabetes using linked administrative data. The development of the Cover Index establishes a novel metric capable of generating fundamental knowledge about health care utilisation patterns that is useful for future research seeking to optimise utilisation of primary health care. This research provides useful evidence for directing primary health care policy.